2011
DOI: 10.1186/1471-230x-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to PPI therapy and factors influencing treatment outcome in patients with GORD: a prospective pragmatic trial using pantoprazole

Abstract: BackgroundManagement of patients with gastro-oesophageal reflux disease (GORD) can be assisted by information predicting the likely response to proton pump inhibitor (PPI) treatment. The aim was to undertake a study of GORD patients designed to approximate ordinary clinical practice that would identify patient characteristics predicting symptomatic response to pantoprazole treatment.Methods1888 patients with symptoms of GORD were enrolled in a multicentre, multinational, prospective, open study of 8 weeks pant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 63 publications
4
48
0
Order By: Relevance
“…79,[110][111][112][113] In a study conducted in patients newly diagnosed with GERD in primary care clinics, partial symptomatic response to PPI therapy was found to be related to women (OR, 1.20; 95% CI, 1.05-1.37). 111 In a systemic review, persistent GERD symptoms despite PPI treatment were more likely to be revealed in women than in men (risk ratio [RR]: 3.66; P < 0.001).…”
Section: Sex/gender and Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…79,[110][111][112][113] In a study conducted in patients newly diagnosed with GERD in primary care clinics, partial symptomatic response to PPI therapy was found to be related to women (OR, 1.20; 95% CI, 1.05-1.37). 111 In a systemic review, persistent GERD symptoms despite PPI treatment were more likely to be revealed in women than in men (risk ratio [RR]: 3.66; P < 0.001).…”
Section: Sex/gender and Treatment Responsementioning
confidence: 99%
“…116 Several recent studies have suggested that women, lower BMI, and psychologic disorders such as anxiety and depression was related to poor response to PPI therapy in patients with GERD, 112,117 while men, obesity, typical reflux symptoms such as heartburn and regurgitation, and alcohol consumption was related to positive therapeutic responses to PPIs in a retrospective study of 683 subjects suspected of GERD who underwent pH-metry/ impedance measurement (pH/MII). 116 It has been suggested that pH/MII (including evaluation of the symptom index) instead of empiric PPI therapy should be considered in non-obese women with atypical reflux symptoms.…”
mentioning
confidence: 99%
“…[5][6][7] Several recent studies suggest that female gender, lower body mass index (BMI), anxiety, and depressive disorders are associated with poor response to PPI treatment in patients with GERD. 8,9 However, response rates and related factors after PPI therapy are significantly different by country. Thus, well-designed studies for assessing the efficacy of PPI therapy in patients with GERD symptoms are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal treatment endurance should be active for a period of between two and eight weeks [4,5]. Supplementary indications include short courses of treatments for prevention of stress ulcers in critically ill patients, as well as for primary and secondary prevention of gastrointestinal haemorrhage.…”
Section: Introductionmentioning
confidence: 99%